LITERATURE GENRES - Ahmatova Mohichexra Mo‘minjon qizi, (Ustozlar uchun, 2025)
This article provides an in-depth exploration of literature genres, examining their definitions, classifications, historical evolution, and cultural significance. It categorizes major genres—fiction, poetry, drama, and non-fiction—along with their subgenres, and analyzes their roles in shaping literary expression and societal values. The article also highlights the development of genres in Uzbek literature, drawing parallels with global literary traditions. By addressing the functions of genres in education, cultural identity, and cross-cultural dialogue, this work serves as a valuable resource for researchers, students, and educators seeking to understand the diversity and impact of literary genres. Particular attention is given to the Uzbek context, where traditional and modern genres coexist to reflect national heritage and contemporary influences.